Deep brain stimulation and multiple sclerosis: Therapeutic applications - Roy, H; Aziz, T (2014)
Deep brain stimulation is a neurosurgical technique that can be used to alleviate symptoms in a growing number of neurological conditions through modulating activity within brain networks. Certain applications of deep brain stimulation are relevant for the management of symptoms in multiple sclerosis. In this paper we discuss existing treatment options for tremor, facial pain and urinary dysfunction in multiple sclerosis and discuss evidence to support the potential use of deep brain stimulation for these symptoms. © 2014 Elsevier B.V. All rights reserved.